Case Analysis of Dispute Resolution in E-Commerce - Fajar Firmansyah (Yayasan Mentari Madani, 2023)
Technological developments make the implementation of trade transactions easier by using the internet, everyone can transact freely. However, the use of technology in e-commerce transactions still has the risk of dispute. The reality occurs in some cases that cause losses felt by the buyer and seller in a buying and selling transaction through e-commerce such as, the goods sent are not in accordance with the order, the buyer is not responsible for payment, the seller cannot be contacted or is not honest in providing information about the goods sold, the goods are lost and damaged at the time of delivery, and other things that often happen in e-commerce transactions